“The Word Black Has Geographic Power”: Itinerant Practices of Black Study in Five Movements - Dahir, Muna (Journal of Critical Race Inquiry, 2026)
This essay was written on the occasion of the 20th anniversary reprint of Demonic Grounds (2026), and the publication of Heartbreak and Other Geographies (2026), a collection of McKittrick’s writing edited by Brittany Meché and Camilla Hawthorne. It pursues some of the lessons that thread through McKittrick’s oeuvre, tracing the knotty threads of Black study that cross and intersect across sites of creative production, knowledge, methods, rebellion, spatial poetics, and scientific stories. On these grounds, I argue that McKittrick, who has long drawn out the deep interconnections between histories of trans-Atlantic slavery, colonialism, land dispossession, colonial modernity, and hierarchized forms of knowledge production, makes visible how reading with and through Black studies reshapes the way we organize and understand knowledge, the world, and ourselves in relation to one another. Through this linked turn to my own encounters and deviating connections across her work and in conversation with others, I highlight how I have learned to read for itinerant forms of Black study through McKittrick’s theories, praxis, and methods. In this way, this essay is an experiment in working with her lessons to demonstrate how Black study is articulated through its plurality, interdisciplinarity, collectivities, and orientation towards imagining more livable futures.